Sustainability of the agri-food supply chain amidst the pandemic: Diversification, local input production, and consumer behavior - Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu (Elsevier, 2021)
This chapter shows how sustainability in agri-food supply chains has been hampered or enhanced during the pandemic. We demonstrate this by applying pathways that producers and consumers in sub-Saharan Africa pursued during the pandemic, as Schmitt et al. (2016) argued. The chapter focuses primarily on two Sub-regions in sub-Saharan Africa: Eastern and Southern Africa. The data used are drawn from a survey conducted by the International Centre for Tropical Agriculture in collaboration with National agricultural research partners in nine countries. Six countries in Eastern Africa countries; Burundi, Democratic Republic of Congo (DRC), Ethiopia, Kenya, Tanzania, and Uganda, and three countries in Southern Africa; Malawi, Zambia, and Zimbabwe. Because of small samples per country and acknowledgment that they are not representational of the status of agri-food systems’ sustainability in the focus countries, we classify them as cases and present them under different sustainability themes: localized input supply and food system sustainability, diversification and Resilience, and consumer behavior.